Determinação bromatológica de pleurotus ostreatus cultivado em resíduos de diferentes cultivares de bananeira - De Carvalho, Cristiane Suely Melo; De Aguiar, Lorena Vieira Bentolila; Sales-Campos, Ceci; De Almeida Minhoni, Marli Teixeira [UNESP]; Andrade, Meire Cristina Nogueira de [UNESP] (My University, 2012)
The objective of this work was to evaluate the nutritional composition (raw protein, ether extract, raw fber, FDA, FDN and ash) of the POS 09/100 strain of Pleurotus ostreatus grown in three combinations of residues (pseudo-stem, leave and pseudo-stem + leaf) and four banana tree cultivars (Thap maeo, Prata anã, Pelipita and Caipira). The basidiomata harvested were submitted to dehydration in a forced ventilation stove with temperature adjusted to 40°C until reaching constant weight, being then grinded in a knife mill. The method proposed by Kjeldahl (1883) was used to determine total nitrogen. The Weende method (AOAC, 1997) was employed to determine crude fber, acid-detergent fber (ADF) and neutral detergent fber (NDF). According to the results obtained, crude protein, ash, ADF and NDF contents varied with the kind of residue and banana tree cultivar; the substrate prepared with leaves of banana tree (Prata Anã cultivar) yielded the highest crude protein (35.4%) and ash (6.7%) contents in the basidiomata of P. ostreatus; the substrate prepared with pseudo-stem of banana tree (Prata Anã cultivar) provided the highest ADF (31.6%) and NDF (41.9%) contents in the basidiomata of P. os - treatus. Ether extract and crude fber contents of P. ostreatus didn't vary in function of the treatments, with averages of 2.45 and 11.27%, respectively.
Bromatological characterization of pleurotus ostreatus grown in different residues from different banana cultivars
Keywords: Pleurotus ostreatus